(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
The growing epidemic of coronary heart disease in Asian countries can be prevented and controlled by identification and management of potentially modifiable risk factors. This article provides a single centre statistics of major modifiable risk factors among Malaysian patients presenting with acute coronary syndrome (ACS) and gives a brief discussion on preventive strategies. A single centre, prospective, observational, cohort study model was used. The subjects were patients of 18 years old or above who were admitted to University Malaya Medical Centre (UMMC), Malaysia within January 2009 to December 2010 and recruited under national ACS registry. Among 1525 consecutive ACS patients, 93% had at least one modifiable risk factor and nearly 70% had three or more risk factors. Overall, the prevalence of risk factors in descending order were: hypertension (70%), smoking (47%), diabetes (43%), dyslipidaemia (23%) and Body Mass Index (BMI)>24 (17%). Majority of male patients were smokers (67%) and most of the females were hypertensives (77%). Hypertension was the strongest predictor of mortality among all ACS patients (odds ratio 2.42, 95% CI, (1.43-4.10)]. Identification and primordial prevention of these risk factors are mandatory for prevention of coronary heart disease in the population. JCMCTA 2014 ; 25 (1): 32-36